Peran Guru dalam Pengembangan Kurikulum Pendidikan Agama Islam - Yusi Srihartini; Mamduh, Duduh; Ahmad Hendrawan; Cut Cory Putri A. (Jurnal Dirosah Islamiyah, 2024)
This research was conducted to determine the role of teachers in the development of Islamic religious education. The method used is a qualitative methodology with data collected through the library research method. The data in this research is based on facts, reality in the field and not designed by researchers through research research. This research aims to evaluate the role of teachers in developing the PAI curriculum, with an emphasis on this theme. This is crucial so that teachers can realize how significant their role is in the curriculum development process, especially amidst the dynamics of rapid change in science and technology. The results of the research can be concluded that the role of the teacher is very large because the success of teaching depends on the teacher's ability and competence in implementing the curriculum effectively. Teachers play a role in developing a curriculum that is managed centrally, decentralized and centrally. Teacher roles include implementer, adapter, developer, and researcher.